Cortical and Subcortical Structural Abnormalities in Patients With Idiopathic Cervical and Generalized Dystonia - Wu, Yunhao; Wang, Tao; Ding, Qiong; Li, Hongxia; Wu, Yiwen; Li, Dianyou; Sun, Bomin; Pan, Yixin (Frontiers in Neuroimaging, 2022)
Objectives: In this study, we sought to investigate structural imaging alterations of patients with idiopathic dystonia at cortical and subcortical levels. The common and specific changes in two subtypes of dystonia, cervical dystonia (CD) and generalized dystonia (GD) were intended to be explored. Additionally, we sought to identify the morphometric measurements which might be related to patients’ clinical characteristics, thus provided more clues of specific brain regions involved in the mechanism of idiopathic dystonia. Methods: T1-weighted MRI scans were acquired from 56 patients with idiopathic dystonia and 30 healthy controls (HC). Cortical thickness (CT) of 30 CD and 26 GD were estimated and compared to HCs using Computational Anatomy Toolbox (CAT12), while volumes of subcortical structures and their shape alterations were analyzed via FSL software. Further, we applied correlation analyses between the above imaging measurements with significant differences and patients’ clinical characteristics. Results: The results of comparisons between two patient groups and HCs were highly consistent, demonstrating increased CT of bilateral postcentral, superiorparietal, superiorfrontal/rostralmiddlefrontal, and occipital gyrus etc., and decreased CT of bilateral cingulate, insula, entorhinal, and fusiform gyrus. (PFWE<0.005 at cluster level). In CD, trends of negative correlations were found between disease severity and CT alterations mostly located in pre/postcentral, rostralmiddlefrontal, superiorparietal and supramarginal regions. Besides, volumes of bilateral putamen, caudate, and thalamus were significantly reduced in both patient groups, while pallidum volume reduction was also presented in GD compared to HCs. Caudate volume reduction had a trend of correlation to increasing disease severity in GD. Last, shape analysis directly demonstrated regional surface alterations in bilateral thalamus and caudate, where the atrophy located in head of caudate had a trend of correlation to earlier ages of onset in GD. Conclusions: Our study demonstrates wide-spread morphometric changes of CT, subcortical volumes and shapes in idiopathic dystonia. CD and GD presented similar patterns of morphometric abnormalities, indicating shared underlying mechanisms in two different disease forms. Especially, the associations of CT of multiple brain regions with disease severity, and altered volume/shape of caudate with disease severity/age of onset separately in CD and GD might serve as potential biomarkers for further disease exploration.